Effectiveness of Physics Learning Using PBL Assisted by PhET Virtual Laboratory - Maulani, Nofrina; Linuwih, Suharto; Sulhadi, Sulhadi (Universitas Negeri Semarang, 2020)
This research is motivated by the lack of digital literacy and the complexity of students in the process of teaching and learning activities. In the learning process during PPKM (Enforcement of Community Activity Restrictions) students do online learning at home, often students who are not active are found. In this case, the teacher's role changes from the main role of providing information to being a facilitator in thinking, reflecting and collaborating findings. The use of PhET virtual laboratory media can help improve technological literacy. The purpose of this study was to analyze the effectiveness of the Problem Based Leaning model assisted by the PhET virtual laboratory on student learning outcomes. PhET simulation is an interactive animation that is accessed online and offline using Java and Flash software. The method used is quantitative research with a one-shot case study design. Class X MIPA 7 was used as the experimental class and class X MIPA 8 was used as the control class. The effectiveness of the Problem Based Leaning model assisted by the PhET virtual laboratory in the experimental class obtained a classical completeness score of 83%, while the control class was far below the classical completeness value of 55%.